2011
DOI: 10.1097/ncc.0b013e31820d0c3f
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Symptoms, Social Support, Uncertainty, and Coping on Health-Related Quality of Life Among Cholangiocarcinoma Patients in Northeast Thailand

Abstract: Cholangiocarcinoma is a unique yet understudied condition. Further work in developing CCA-specific HRQOL interventions is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…In the Thai cultural context, social support from family and neighbors may have led to an improvement in social/family and emotional well-being domains. The finding is similar to that of the cross-sectional study of CCA patients in Northeastern Thailand, 13 in which the highest QOL scores of CCA patients were in the emotional well-being and social/family well-being domains. In a study of HCC patients in the United States, 11 the patients had lower HRQOL scores than did the general population, but the scores were highest in the social/family well-being domain.…”
Section: N Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the Thai cultural context, social support from family and neighbors may have led to an improvement in social/family and emotional well-being domains. The finding is similar to that of the cross-sectional study of CCA patients in Northeastern Thailand, 13 in which the highest QOL scores of CCA patients were in the emotional well-being and social/family well-being domains. In a study of HCC patients in the United States, 11 the patients had lower HRQOL scores than did the general population, but the scores were highest in the social/family well-being domain.…”
Section: N Discussionsupporting
confidence: 90%
“…11,12 Hepatocellular carcinoma patients differ in several respects from those with CCA, and with respect to the latter, only 1 cross-sectional study (in northeast Thailand) has been reported. 13 It investigated factors influencing HRQOL of CCA patients, with an emphasis on symptoms, social support, uncertainty, and coping. The present study was conducted to investigate the associations among demographic, clinical, treatment factors and HRQOL in CCA patients.…”
mentioning
confidence: 99%
“…psycho-social issues as a consequence of cancer diagnosis and treatment: (a) symptoms and side effects of chemotherapy [11], (b) fear of recurrence [12], (c) financial difficulty [13], (d) lack of adequate guidance on diet and physical activity [14], (e) adverse changes of familial and social relationships [15] and (f) inability to adjust life after cancer [16]. As discussed in previous studies, a myriad of psycho-social intervention approaches, such as cognitivebehavioural interventions [17], counselling [18], relaxation training [19], stress management and support group interventions [20,21], have acted positively in alleviating psychological morbidity and improving the quality of life in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, that uncertainty will increase when symptoms exacerbate and the disease progresses or when the pattern of symptoms cannot be predicted. 36,38 Those authors also found that patients with higher uncertainty had significantly lower HRQOL.…”
Section: Regret Ever Starting Treatmentmentioning
confidence: 88%
“…The influence of symptoms on uncertainty has been described in studies with patients with other cancers (breast, cholangiocarcinoma, and head and neck). 36Y38 In the study of patients with cholangiocarcinoma by Somjaivong et al, 36 symptoms had a direct effect on uncertainty. The authors suggest that symptoms may be associated with the unpredictability of an illness trajectory.…”
Section: Regret Ever Starting Treatmentmentioning
confidence: 98%